2011
DOI: 10.1038/mi.2010.90
|View full text |Cite
|
Sign up to set email alerts
|

Urothelial antigen-specific CD4+ T cells function as direct effector cells and induce bladder autoimmune inflammation independent of CD8+ T cells

Abstract: The role of CD4+ T cells in bladder autoimmune inflammation has not been identified due to the lack of a proper animal model. We investigated CD4+ T cell responses to bladder urothelial ovalbumin (OVA), a model self-antigen (Ag), in transgenic URO-OVA mice. The expression of bladder urothelial OVA rendered mice unresponsive to OVA and resulted in quick clearance of Ag-specific CD4+ T cells. Adoptive transfer of naïve OVA-specific CD4+ T cells led to exogenous T cell proliferation, activation, and bladder infil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…In present study, CD4 + Tcells had a larger scale in ltration in BLCA tissue from high-risk group than lowrisk group, but CD8 + had no difference. One study conducted by Liu W et al had revealed that urothelial antigen-speci c CD4 + T cells function as direct effector cells and induce bladder autoimmune in ammation independent of CD8 + T cells, which coincided with our nding [58].…”
Section: Discussionsupporting
confidence: 88%
“…In present study, CD4 + Tcells had a larger scale in ltration in BLCA tissue from high-risk group than lowrisk group, but CD8 + had no difference. One study conducted by Liu W et al had revealed that urothelial antigen-speci c CD4 + T cells function as direct effector cells and induce bladder autoimmune in ammation independent of CD8 + T cells, which coincided with our nding [58].…”
Section: Discussionsupporting
confidence: 88%
“…In addition to CD8 + T cells, CD4 + T cells are capable of inducing EAC in the URO‐OVA mice. We observed that adoptive transfer of OT‐II CD4 + T cells that express the transgenic TCR specific for the I‐A b /OVA 323–339 epitope peptide induced EAC in the URO‐OVA mice 128 . Our studies showed that antigen‐specific CD4 + T cells functioned as direct effector cells and induced EAC independent of CD8 + T cells.…”
Section: Animal Modelsmentioning
confidence: 60%
“…Recently, several studies using transgenic mouse models that expressed various model autoantigens demonstrated that autoantigen‐specific T cells induced autoimmune diseases. For example, OVA‐specific CD4 + T cells induced bladder autoimmune inflammation in transgenic URO‐OVA mice that express the model self‐antigen OVA on the bladder urothelium . A study using skin‐directed expression of OVA demonstrated that GVHD‐like inflammatory skin disease was induced by transferring OVA‐specific OT‐I CD8 + T cells .…”
Section: Discussionmentioning
confidence: 99%
“…For example, OVA-specific CD4 1 T cells induced bladder autoimmune inflammation in transgenic URO-OVA mice that express the model self-antigen OVA on the bladder urothelium. 29 A study using skin-directed expression of OVA demonstrated that GVHD-like inflammatory skin disease was induced by transferring OVA-specific OT-I CD8 1 T cells. 30 Furthermore, transfer of OT-I T cells led to cholangitis in the liver of transgenic mouse in which the model antigen OVA was expressed in cholangiocytes.…”
Section: Discussionmentioning
confidence: 99%